1997
DOI: 10.1080/03079459708419201
|View full text |Cite
|
Sign up to set email alerts
|

Swollen head syndrome in broiler chickens in Japan: Its pathology, microbiology and biochemistry

Abstract: SUMMARYFour-to-seven-week-old broilers with swollen head syndrome (SHS) from 4 different districts of Japan were examined for pathological, microbiological and biochemical findings. Periocular and mandibular subcutaneous swelling, sometimes accompanied by ocular, hepatic and cardiac lesions were observed. Histologically, diffuse fibrinopurulent inflammation with focal granulomatous lesions was characteristic of subcutaneous tissue of the head, especially periocular tissue. The air spaces of the cranial bones a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0
10

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 27 publications
3
14
0
10
Order By: Relevance
“…There was no lesion in the trachea. Similar lesions were reported by many investigators (Nakamura et al, 1997;Rocio et al, 1998;Murakami et al, 2002;Jaswinder et al, 2005). (41.4%) were isolated from trachea and nasal sinuses of chickens.…”
Section: Histopathological Studysupporting
confidence: 76%
“…There was no lesion in the trachea. Similar lesions were reported by many investigators (Nakamura et al, 1997;Rocio et al, 1998;Murakami et al, 2002;Jaswinder et al, 2005). (41.4%) were isolated from trachea and nasal sinuses of chickens.…”
Section: Histopathological Studysupporting
confidence: 76%
“…Our findings reveal that virus replication in the sinus tissue is substantial and causes microscopical changes from 4 to 10 d.p.i., followed by deciliation, which lasts even longer. These observations could support the work of Nakamura et al (1997) who described the pathology of swollen head syndrome in broiler chickens, some of which were serologically positive for TRT, whilst in others TRT antigen was detected using a reverse transcriptase polymerase chain reaction. They suggested that sinusitis appears to induce Escherichia coli proliferation in the subcu- taneous tissue as a result of destruction of respiratory epithelium and that TRT virus is a candidate for causing the initial damage.…”
Section: (A) Hyperaemia and Inflammatory Cellular Infiltration Of supporting
confidence: 74%
“…In Experiment 1, four strains of E. coli were used: TK 736 (serotype 02) from a liver of a chicken with perihepatitis, 139-A (serotype 078) from an air sac with airsacculitis, and TOK-1 and IBA-1 (untypable) from skin of a SHS case (Nakamura et al, 1997). In Experiment 2, TK 736 strain was used.…”
Section: Escherichia Colimentioning
confidence: 99%
“…TRT virus, a pneumovirus, has been strongly implicated as a factor in SHS in chickens (Naylor & Jones, 1993). Escherichia coli has been consistently isolated from skin lesions of the head (Morley & Thomson, 1984;O'Brien, 1985;Pattison et al, 1989;Uramoto et al, 1990;Droual & Woolcock, 1994;Tanaka et al, 1995;Nakamura et al, 1997). Therefore, E. coli is thought to be a secondary complicating factor (Naylor & Jones, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation